Ρenetapan Denda Keterlambatan Iuran Penyelenggaran Jaminan Sosial Kesehatan dalam Perspektif Fatwa DSN MUI NO. 98/DSN-MUI/XII/2015 - Jelita Harahap; Mhd. Yadi Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
BPJS Kesehatan is an institution established to provide national health insurance based on social insurance. However, in its implementation, BPJS Kesehatan reaps the pros and cons. so, the author feels that BPJS Kesehatan still needs a more in-depth study, especially related to the imposition of fines by referring to Fatwa DSN-MUI Number 98 of 2015. The formulation of the problem of this research is how the provisions of fines sanctions according to Fatwa DSN-MUI Number 98 of 2015 Number 8 paragraph (1), points a, b and c regarding Provisions related to Sanctions. how the application of fines for late BPJS contributions according to Presidential Regulation No. 64 of 2020. The research method used by Yuridis Normatif with a statutory approach is carried out by examining all laws and regulations related to the legal issues being studied that occur in the field. the conclusion of this research shows that based on the 2015 MUI DSN Fatwa decision regarding the application of late payment fines for BPJS Health, MUI Classifies the application of late fines to the implementation of BPJS Health.